Trends in Antibiotic Duration for Complicated Intra-Abdominal Infections: Adaptation to Current Guidelines. Issue 1 (January 2021) - DeCesare, Laura; Xu, Thomas Q.; Saclarides, Constantine; Coughlin, Julia M.; Chivukula, Sitaram V.; Woodfin, Ashley; Chan, Edie; Booker, Connor; Jacobson, Richard
Introduction: The 2017 surgical infection society (SIS) guidelines recommend 4 days of antibiotic therapy after source control for complicated intra-abdominal infections (cIAIs). Inappropriate exposure to antibiotics has a negative impact on outcomes in individual patients and populations. The goal of this study was to evaluate our institution's practice patterns and adherence to current antibiotic guidelines. Methods: Medical records from 2010 to 2018 for cIAIs were examined. Complicated appendicitis and complicated diverticulitis cases were included. Exclusion criteria included other etiologies of IAIs, pediatric cases, and cancer operations. Results: Fifty-nine complicated appendicitis cases and 96 complicated diverticulitis cases were identified. For all cases, antibiotic duration prior to publication of the SIS guidelines was significantly longer than post-SIS duration (appendicitis: 12.6 ± 1.1 days pre-SIS [n = 37] vs 9.0 ± 1.1 days post-SIS [n = 22], P = .01; diverticulitis: 15.1 ± 0.8 days pre-SIS [n = 49] vs 11.2 ± 0.5 post-SIS [n = 47], P = .04). Surgical management (SM) was associated with shorter duration of postsource control antibiotic exposure compared with percutaneous drainage (PD) for both appendicitis (SM 10.0 ± 1.2 days vs PD 13.4 ± 1.0 days, P = .02) and diverticulitis (SM 12.8 ± 1.5 days vs PD 16.0 ± 1.5, P = .07). Patients with complicated appendicitis received shorter duration of antibiotics when managed by acute care surgeons compared to general surgeons (8.4 ± 1.1 vs 11.9 ± 0.8, P = .02). Conclusion: Despite improvements after the SIS guidelines' publication, the antibiotic duration is still longer than recommended. Surgical intervention and management by acute care specialists were associated with a shorter duration of antibiotic exposure.